2019
DOI: 10.5530/jscires.8.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Google Scholar Citations: A Size-independent Institution-based Analysis

Abstract: Most currently available schemes for performance-based ranking of Universities/ Research organizations, such as, Quacarelli Symonds (QS), Times Higher Education (THE), Shanghai University-based All Research of World Universities (ARWU) use a variety of criteria that include productivity, citations, awards, reputation, etc., while Leiden and Scimago use only bibliometric indicators. The research performance evaluation in the aforesaid cases is based on bibliometric data from Web of Science or Scopus, which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This might be due to science being abstract and is much more difficult to measure tan any physical product, which has led to studies that have compared the positions that universities occupy in rankings. Some such studies have found a high correlation among the positions occupied by universities in ARWU, QS, and THE [2,3,7,8], and a low correlation of three GURs with Webometrics [3]. However, this work analyzed the geographical distribution of the universities in the Top 500 of the four studied GURs and evidences a different occupancy in them according to regions either for each quartile or the total of universities.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…This might be due to science being abstract and is much more difficult to measure tan any physical product, which has led to studies that have compared the positions that universities occupy in rankings. Some such studies have found a high correlation among the positions occupied by universities in ARWU, QS, and THE [2,3,7,8], and a low correlation of three GURs with Webometrics [3]. However, this work analyzed the geographical distribution of the universities in the Top 500 of the four studied GURs and evidences a different occupancy in them according to regions either for each quartile or the total of universities.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, the Webometrics ranking has been analyzed with the three other GURs by two works. One work [3] has studied the correlation among the four GURs, and that with two others, namely Leiden and Scimago. As expected, the higher correlations appear among ARWU, THE and QS, and among Webometrics, Leiden and Scimago.…”
Section: Ranking Web Of Universities or Webometrics Ranking Of World Universitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, WoS has an average error rate of 0.1% [ 4 , 18 , 31 , 32 ], and this rate is 1.0% for Scopus [ 10 , 31 ]. However, since GS is a free database [ 56 ], it may be the only possible way to conduct a study. However, knowing that all databases are likely to contain errors, verifying a sample of data is a useful precaution.…”
Section: Discussionmentioning
confidence: 99%